Exercise and nutritional interventions on sarcopenia and frailty in heart failure: a narrative review of systematic reviews and meta‐analyses. (15th July 2022) - Prokopidis, Konstantinos; Isanejad, Masoud; Akpan, Asangaedem; Stefil, Maria; Tajik, Behnam; Giannos, Panagiotis; Venturelli, Massimo; Sankaranarayanan, Rajiv
Abstract: The purpose of this review is to describe the present evidence for exercise and nutritional interventions as potential contributors in the treatment of sarcopenia and frailty (i.e. muscle mass and physical function decline) and the risk of cardiorenal metabolic comorbidity in people with heart failure (HF). Evidence primarily from cross‐sectional studies suggests that the prevalence of sarcopenia in people with HF is 37% for men and 33% for women, which contributes to cardiac cachexia, frailty, lower quality of life, and increased mortality rate. We explored the impact of resistance and aerobic exercise, and nutrition on measures of sarcopenia and frailty, and quality of life following the assessment of 35 systematic reviews and meta‐analyses. The majority of clinical trials have focused on resistance, aerobic, and concurrent exercise to counteract the progressive loss of muscle mass and strength in people with HF, while promising effects have also been shown via utilization of vitamin D and iron supplementation by reducing tumour necrosis factor‐alpha (TNF‐a), c‐reactive protein (CRP), and interleukin‐6 (IL‐6) levels. Experimental studies combining the concomitant effect of exercise and nutrition on measures of sarcopenia and frailty in people with HF are scarce. There is a pressing need for further research and well‐designed clinical trials incorporating the anabolic and anti‐catabolic effects of concurrent exercise and nutrition strategies in people with HF.